2(9s+10)-3s=3(5s+2)-10

Simple and best practice solution for 2(9s+10)-3s=3(5s+2)-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(9s+10)-3s=3(5s+2)-10 equation:


Simplifying
2(9s + 10) + -3s = 3(5s + 2) + -10

Reorder the terms:
2(10 + 9s) + -3s = 3(5s + 2) + -10
(10 * 2 + 9s * 2) + -3s = 3(5s + 2) + -10
(20 + 18s) + -3s = 3(5s + 2) + -10

Combine like terms: 18s + -3s = 15s
20 + 15s = 3(5s + 2) + -10

Reorder the terms:
20 + 15s = 3(2 + 5s) + -10
20 + 15s = (2 * 3 + 5s * 3) + -10
20 + 15s = (6 + 15s) + -10

Reorder the terms:
20 + 15s = 6 + -10 + 15s

Combine like terms: 6 + -10 = -4
20 + 15s = -4 + 15s

Add '-15s' to each side of the equation.
20 + 15s + -15s = -4 + 15s + -15s

Combine like terms: 15s + -15s = 0
20 + 0 = -4 + 15s + -15s
20 = -4 + 15s + -15s

Combine like terms: 15s + -15s = 0
20 = -4 + 0
20 = -4

Solving
20 = -4

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 234234X+234234X= | | 2.4+0.4x=0.25(6+x) | | 6(x+5)=3(2x+4)+18 | | .8(x+40)+.2x=57 | | 24x+5x+67=24 | | 5d^2+5d-6=0 | | 12(3x+3)-7(2x-3)=12x-13 | | a=1b | | X=32+-3x | | .70x+.05(2-x)=.10(-64) | | (p+36)+p+(4p-37)=677 | | 3x=x+36 | | 3x=x+32 | | (5-c)(5+c)=0 | | .30(12)+.05x=.10(6+x) | | 3(6-3m)+5(2m+7)=0 | | 5c^2+5c+15=0 | | 25-c^2=0 | | (2/3)x=5(1/3) | | 9x=810 | | 2d-14=-24 | | 10x^2+5x-1=0 | | 3x=32 | | 10x^2+5y-1=0 | | -10=-3m+5 | | (3/4)8=x | | 3x-8=6x-26 | | x+6x=23 | | 3x-x=x+20 | | c/4=1/2 | | 10x-y*x-x^2-.5x^3=0 | | 2(3y-5)=-15 |

Equations solver categories